A SENSITIVE STAINING METHOD FOR NORS - YEKELER, H; EREL, O; YUMBUL, AZ; DOYMAZ, MZ; DOGAN, O; OZERCAN, MR; IPLIKCI, A (John Wiley & Sons Ltd, 1995)
A sensitive staining method for nucleolar organizer regions (NORs) is described, using blue toning of AgNORs. NORs are loops of DNA which are transcribed into ribosomal RNA. NORs can be demonstrated by staining with silver nitrate, since NOR-associated proteins are argyrophilic, producing structures termed AgNORs. Normal blood lymphocytes were stained with both methods. The number and resolution of NORs increased 2-3 times by blue toning (30 mmol/l FeCl3, 11 mmol/l potassium hexacyanoferrate(III), and 33 mmol/l oxalic acid) compared with silver staining. A significant difference in the number of NORs was noticed between silver-stained and blue-toned cells (P<0.001). The blue toning technique thus appears to be more sensitive in detecting NORs than the AgNOR method and may prove a useful alternative for applications in histopathology.
Keywords: NOR; AGNORS; BLUE TONING; LYMPHOCYTES